2003
DOI: 10.1080/07391102.2003.10506917
|View full text |Cite
|
Sign up to set email alerts
|

The NMR-Derived Conformation of Orexin-A: An Orphan G-Protein Coupled Receptor Agonist Involved in Appetite Regulation and Sleep

Abstract: The conformation of orexin-A, an orphan G-protein coupled receptor agonist has been determined when bound to sodium dodecylsulphate-d(25) (SDS) micelles by (1)H and (13)C NMR and molecular modeling. Orexin-A has been implicated in sleep-wakefulness and feeding regulation. The conformational preference of orexin-A consists of a short helical section, involving Asp(5) to Gln(9) that makes up helix I, followed by a bend from Lys(10) to Ser(13). Residues Leu(16) to Gly(22) make up helix II. The conformation of ore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Due to spectral overlap and lack of many NOE restraints, it was difficult to determine the structure of functionally important C-terminal region in SDS micelles. Miskolzie and Kotovych [62] have predicted that this segment might adopt a turn-like or short helical structure. In contrast to the micelle structure, C-terminal region of orexin-A is clearly helical in solution (PDB codes: 1WSO and 1R02).…”
Section: Orexin Peptidesmentioning
confidence: 98%
See 1 more Smart Citation
“…Due to spectral overlap and lack of many NOE restraints, it was difficult to determine the structure of functionally important C-terminal region in SDS micelles. Miskolzie and Kotovych [62] have predicted that this segment might adopt a turn-like or short helical structure. In contrast to the micelle structure, C-terminal region of orexin-A is clearly helical in solution (PDB codes: 1WSO and 1R02).…”
Section: Orexin Peptidesmentioning
confidence: 98%
“…The absence of orexin peptides in the patient results in narcolepsy, a chronic sleep disorder [150]. Structures of both the orexin peptides have been determined in SDS micelles [52,62] as well as in solution [151].…”
Section: Orexin Peptidesmentioning
confidence: 99%
“…NMR and computational studies performed on orexin A (in aqueous 25 and in membrane mimetic micellar solutions 26 ) identified a highly conserved hydrophobic region on the C-terminus. This region contains two α-helices that are connected by a short linker.…”
mentioning
confidence: 99%
“…NMR and computational studies performed on orexin A (in aqueous and in membrane mimetic micellar solutions) identified a highly conserved hydrophobic region on the C-terminus. This region contains two α-helices that are connected by a short linker. , Similarly, solution structure of orexin B (in aqueous and in micellar solution) also shows two α-helices at similar positions.…”
mentioning
confidence: 99%
See 1 more Smart Citation